If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + -6v = 7(7 + -2v) -7 + -6v = (7 * 7 + -2v * 7) -7 + -6v = (49 + -14v) Solving -7 + -6v = 49 + -14v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '14v' to each side of the equation. -7 + -6v + 14v = 49 + -14v + 14v Combine like terms: -6v + 14v = 8v -7 + 8v = 49 + -14v + 14v Combine like terms: -14v + 14v = 0 -7 + 8v = 49 + 0 -7 + 8v = 49 Add '7' to each side of the equation. -7 + 7 + 8v = 49 + 7 Combine like terms: -7 + 7 = 0 0 + 8v = 49 + 7 8v = 49 + 7 Combine like terms: 49 + 7 = 56 8v = 56 Divide each side by '8'. v = 7 Simplifying v = 7
| -6+18y=-12-8+19y | | 1+n+n=n-1 | | 11.41-0.7b=11.1b+17.31 | | 6+2(x+1)=2x+8 | | -18.9r-14.16=-18r-2.46 | | (5y-8)+(11x-9)=180 | | R/8=96 | | -8f-10=-9f | | f+2=-3-4f | | -18z=6-19z | | 5g=8-y | | 66+b=99 | | -8-2x=-8x+14 | | (5x-8)+(11x-9)=180 | | 19w-9(15w+1)=20w-9-8w | | -1-15u=13-17u+16 | | -5d-10=10+5d | | 6x-12=3x+11 | | 6h-16h-6=-11h-16 | | 22+3x=x+10 | | 3.8s=9.36+4.4s | | M=3(x+4) | | 10+14m=8m-14 | | 6+4k=6(1+7k) | | 65/8-23/8 | | -17.3p-19.19=-3.8-14.7p+9.31 | | -18.66+4m=15.2m+2.14-9.2m | | 3n-2=-7+2n | | 2c=44 | | 4-10j=3(-7j+16) | | -4-2r=-3r | | -2/3-x-6/6=1/3 |